KONTRIBUSI ALUMNI PGMI FITK UIN RADEN FATAH DALAM UPAYA MEMBANGUN PENDIDIKAN DI PERBATASAN SUMATERA SELATAN (STUDI MULTISITUS OKU SELATAN DAN EMPAT LAWANG) - Amir Hamzah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2018)
Abstract South Sumatra is one of the province in Indonesia which is located in the southern of the Sumatra Island . This capital of this Province is Palembang. Geographically, South Sumatra borders with Jambi province at the north, Kepulauan Bangka-Belitung province at the east, and with Lampung province at the south and Bengkulu province at the west. South Sumatra experiences the development in education. It can be seen from year to year in South Sumatra. There are always national and international events as a form of national and international community trust. PGMI Alumni, Faculty of Teacher Training and Education at UIN Raden Fatah is a bachelor program in charge of Madrasah Ibtidaiyah / Elementary Education in ​​South Sumatra. The purpose of this study is to determine the role of PGMI alumni in education development of South Sumatra. The implementation of PGMI alumni in the field of Madrasah Ibtidaiyah and theobstacles that are experienced by PGMI alumni at the South Sumatra border, and the solutions that can be given to the South Sumatra as a multisite study (South OKU and Empat Lawang) The study was conducted with a qualitative approach. Qualitative approaches are strategies and research techniques that are used to understand the community, problems or symptoms in the community by collecting as many in-depth facts as possible. Data are presented in verbal form rather than numerical forms. This research used two places namely South OKU and Empat Lawang (Multisite) The contributions of alumni at the border are working in the district in various sectors ranging from Government, Education, and Society. The role of alumni in the Madrasah Ibtidaiyah is in 2013 Curriculum Development, the development of media of learning, enhancement of extracurricular activities in elementary schools, and the learning of Tahfiz Qur’an juz 30. The obstacles that are faced by alumni are the gap between PGSD and PGMI alumni in several regions, facilities, lack of communication, parents' economics / the role of parents is not too effective and the development of child psychology